2022
DOI: 10.1093/jacamr/dlac033
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying the emergence of polygenetic antifungal drug resistance in msh2 mismatch repair mutants of Cryptococcus

Abstract: Background Fungal infections are common life-threatening diseases amongst immunodeficient individuals. Invasive fungal disease is commonly treated with an azole antifungal agent, resulting in selection pressure and the emergence of drug resistance. Antifungal resistance is associated with higher mortality rates and treatment failure, making the current clinical management of fungal disease very challenging. Clinical isolates from a variety of fungi have been shown to contain mutations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…The emergence of resistance to flucytosine prevents its use as a monotherapy drug for cryptococcosis antifungal treatment, so it is used in combination with amphotericin B as a first-line induction treatment, as cited previously [ 40 ]. The process leading to the emergence of fluconazole resistance in Cryptococcus SC is challenging to identify, and many studies are dedicated to elucidating it [ 65 ].…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…The emergence of resistance to flucytosine prevents its use as a monotherapy drug for cryptococcosis antifungal treatment, so it is used in combination with amphotericin B as a first-line induction treatment, as cited previously [ 40 ]. The process leading to the emergence of fluconazole resistance in Cryptococcus SC is challenging to identify, and many studies are dedicated to elucidating it [ 65 ].…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…In addition, the emergence of drug resistance is not limited to mutations in the above genes. By identification of deletion mutants and determination of ploidy changes through whole-genome sequencing (WGS), Albehaijani found that only MSH2 gene mutations occurred in the genome of drug-resistant strains, and no mutations in ERG11 or other genes of the ergosterol biosynthesis pathway were involved [15] . Boyce et al .…”
Section: Drug-resistance Mechanisms Of Cryptococcusmentioning
confidence: 99%
“…Notably, MMR pathway proteins have also been associated with drug resistance and hypermutable phenotypes in other important fungal pathogens, Cryptococcus spp. and A. fumigatus [ 80 , 81 , 82 , 83 , 84 ]. Similarly, a mutation in the DNA polymerase delta subunit-encoding POL3 gene led to a hypermutator phenotype in Cryptococcus deneoformans , with this mutation being mapped to the exonuclease proofreading domain [ 85 ].…”
Section: Role Of Dna-damage Repair Mechanisms In Antifungal Resistancementioning
confidence: 99%